Edutainment Teaching Technique and Students’ Skills Performance in Building Drawing in Technical Colleges in Akwa Ibom State - , A. D. Usoro; , Otu, Ebeten Bassey (Archives of Current Research International, 2019)
The study was on edutainment technique and students’ skills performance in building drawing in Technical Colleges in Akwa Ibom State. The study sought to find the effect of edutainment technique and demonstration method on students’ performance in building drawing. Three research questions and null hypotheses were formulated to guide the study. A quasi-experimental design was adopted for the study. The population used for the study was three hundred and eighty (380) senior technical college II students in all the seven (7) public Technical Colleges in Akwa Ibom State. The sample comprised one hundred and ten (110) students drawn from two (2) intact classes. A 30-item multiple-choice performance test called Performance Test on Building Drawing (PTBD) was developed to determine performance level of the control and experimental groups and building drawing lesson plan for the treatment of the experimental group. The instrument was validated by three experts. Two from the Department of Vocational Education, one from Test and Measurement Unit of the Department of Educational Foundations. Cronbach alpha reliability was used to determine the internal consistency of the instrument. The instrument yielded a reliability coefficient of 0.86. Mean and standard deviation were used to answer research questions while analysis of covariance was used to test the null hypotheses at .05 level of significance. The results showed that students taught using edutainment technique have higher mean scores than those taught with demonstration method. It also showed that the mean score of male students was slightly higher than that of female students in the experimental group. The post-test analysis on Building Drawing Performance Test (PTBD) was in favour of the experimental group. However, there was no significant difference between males and females on building drawing performance test as a result upon treatment. Based on these results, it was recommended among others that edutainment technique should be adopted by building drawing teachers in teaching building drawing in Technical Colleges in Akwa Ibom State to solve the problem of poor performance of students.